1995
DOI: 10.1159/000178971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pentobarbital, Propofol and Ketamine on Skeletal Muscle Capillary Perf usion during Hemorrhage: A Comparative Study in the Rabbit

Abstract: Anesthetics affect tissue blood flow, which is of importance especially in situations of inadequate perfusion, as in hemorrhage. The present study compared the effect of three commonly used anesthetic agents on skeletal muscle capillary and regional blood flow during and after recovery from hemorrhage. Three groups of rabbits were anesthetized randomly with either pentobarbital, propofol or ketamine, chosen such that the anesthetic level, blood pressure and withdrawn blood volume were comparable in all groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…26 These observations are in agreement with previous studies in skeletal muscle, demonstrating well-maintained capillary perfusion with ketamine anaesthesia. 28 Constriction of arterioles and venules may have also maintained hydrostatic pressure and prevented¯uid loss into the mesenteric extravascular space and hence, the abdomen. Interestingly, after haemorrhage¯uid absorption appeared to be greater during ketamine anaesthesia, 29 as indicated in the present study by the greater decrease in haematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…26 These observations are in agreement with previous studies in skeletal muscle, demonstrating well-maintained capillary perfusion with ketamine anaesthesia. 28 Constriction of arterioles and venules may have also maintained hydrostatic pressure and prevented¯uid loss into the mesenteric extravascular space and hence, the abdomen. Interestingly, after haemorrhage¯uid absorption appeared to be greater during ketamine anaesthesia, 29 as indicated in the present study by the greater decrease in haematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used anesthetic is propofol. In an experiment by Gustafsson et al [1995], the effects of three popular anesthetics on skeletal muscle capillary and regional blood flow were compared. This study indicated that ketamine maintained capillary perfusion the best, followed by pentobarbital and then propofol.…”
Section: Effect Of Anesthetics On Microcirculation and Microvasculaturementioning
confidence: 99%
“…In the present study, only the anesthetized groups showed low pH values and higher plasma [K ϩ ]. Finally, the absence of significant differences in MAP between anesthetized groups suggests that ketamine could prevent the development of tissue hypoxia during hemorrhage by affecting peripheral cardiovascular mechanisms rather than central cardiovascular control (14,26). A better peripheral vascular condition in KA rats would be reflected in the present study as an acid-base behavior intermediate between C and UA rats.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies have addressed questions on the peripheral circulatory actions of anesthetics during hemorrhage, but there is little specific information about their acid-base effects during hemorrhagic shock in rats. Ketamine is widely used in studies on hemorrhage in several species (14,15,26,36), whereas urethan has been used to a lesser extent (33). An additional goal of the present study was to compare the evolution of acid-base changes during hemorrhage in rats anesthetized with ketamine or urethan with respect to that found in conscious hemorrhaged rats.…”
Section: ϫmentioning
confidence: 98%
See 1 more Smart Citation